2015
DOI: 10.1097/qai.0000000000000712
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Tuberculosis Among Adults Newly Diagnosed With HIV in Sub-Saharan Africa

Abstract: Objective New tools, including light emitting diode (LED) fluorescence microscopy and the molecular assay Xpert MTB/RIF® offer increased sensitivity for TB in persons with HIV but come with higher costs. Using operational data from rural Malawi we explored the potential cost-effectiveness of on-demand screening for TB in low-income countries of sub-Saharan Africa. Design & Methods Costs were empirically collected in four clinics and one hospital using a micro-costing approach, through direct interview and ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 21 publications
1
19
1
Order By: Relevance
“…Our scenario analysis result also revealed that the cost of both diagnostic algorithms was reduced from the base case estimate by increasing the volume of tests per day. This cost estimate is in line with nding from sub-Sahara Africa [29] and Uganda [30] on the cost and cost-effectiveness of the GeneXpert diagnostic test. The cost of the test method was high in health facilities where their testing volume was low.…”
Section: Discussionsupporting
confidence: 82%
“…Our scenario analysis result also revealed that the cost of both diagnostic algorithms was reduced from the base case estimate by increasing the volume of tests per day. This cost estimate is in line with nding from sub-Sahara Africa [29] and Uganda [30] on the cost and cost-effectiveness of the GeneXpert diagnostic test. The cost of the test method was high in health facilities where their testing volume was low.…”
Section: Discussionsupporting
confidence: 82%
“…Few studies have estimated the economic effect of implementing Xpert at the point of care 22,25,26 and all have used modelling analyses rather than prospectively obtained trial data to assess cost-effectiveness. 19,20,24,25,35 In most of these modelling studies, Xpert was cost-effective either as a full replacement 19,24,25,35 or in conjunction with other diagnostic tests 20,21 compared with the standard of care (smearmicroscopy). However, some of these studies did not incorporate empirical treatment and thus might have overestimated the effectiveness of Xpert.…”
Section: Discussionmentioning
confidence: 99%
“…However, some of these studies did not incorporate empirical treatment and thus might have overestimated the effectiveness of Xpert. 24,25 Our estimates of cost-effectiveness account for levels of empirical treatment observed in the TB-NEAT trial and require fewer modelling assumptions than these previous analyses but might, there fore, underestimate the effectiveness of point-of-care Xpert by not explicitly accounting for effects on secondary transmission. Conversely, clinical trials can provide direct and real-world data on patient important outcomes related to Xpert implementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we looked at patient volume, which determined the number of tests done per day. Test volume has been found to be a major factor in the cost-effectiveness of POC tests [13, 14]. The baseline scenario used the total number of patients enrolled in both arms as the volume.…”
Section: Methodsmentioning
confidence: 99%